2005
DOI: 10.1007/s10551-004-8205-4
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical and Theoretical Exploration of Disconnections Between Leadership and Ethics

Abstract: A comparison of two groups of college students, at a public state university and a private religious school, yields the same results: undergraduates' interpretations of recent business scandals make distinctions between public and private behavior. Students admire ''family men'' even when they are caught at fraud. The students' interpretations illustrate a significant gap in ethical theories: the benefits of a group perspective for corporate citizenship versus individual family values. Most leadership theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…As suggested above, an important reason here is the change in the institutional environments in the hospitality industry, which can influence organizational institutions and determine their legitimacy. This echoes the point we made at the outset: good leaders should come equipped with ethics-or else they should not be considered good leaders (Brown and Treviño 2006;Hornett and Fredericks 2005), and this point certainly applies to the hospitality industry. Let us examine this study's theoretical and practical implications.…”
Section: Discussionmentioning
confidence: 72%
“…As suggested above, an important reason here is the change in the institutional environments in the hospitality industry, which can influence organizational institutions and determine their legitimacy. This echoes the point we made at the outset: good leaders should come equipped with ethics-or else they should not be considered good leaders (Brown and Treviño 2006;Hornett and Fredericks 2005), and this point certainly applies to the hospitality industry. Let us examine this study's theoretical and practical implications.…”
Section: Discussionmentioning
confidence: 72%
“…Although there have been a notable number of recent scandals involving ethically questionable behavior of business leaders (Hornett and Fredricks, 2005), the scandal that has attracted the most media attention involved the Enron Corporation. By the year, 2000 Enron was the seventh largest company in the United States (Morse and Bower, 2002) and one of the most admired (McLean and Elkind, 2003).…”
Section: Landmark Scandals and Leader Accountabilitymentioning
confidence: 99%
“…Prior research by the team who designed this study had suggested that a perception of a relationship between a person and someone affected by their ethical choice can alter ethical responses (Hornett and Fredricks, 2005;Fredricks and Hornett, 2007). Using a survey based in real-life-derived scenarios about a supermarket theft and a workplace fraud, the prior research found that undergraduate students in US universities were statistically likely to change their course of action when a social relationship was introduced -that is, they were more likely to behave ethically if they felt that a relative, even a distant one, would be detrimentally affected by an unethical choice.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the process of discussion itself changed students' thinking about ethics and enhanced mutual understanding (Hornett and Fredricks, 2005). Jovanovic and Wood (2006, p. 386) concur: "talk about ethics contributes to an ethical culture".…”
Section: The Relationship Effectmentioning
confidence: 99%